2008
DOI: 10.1016/j.neuroimage.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of statistical power for continuous arterial spin labeling imaging at 1.5 T

Abstract: Variance estimates can be used in conjunction with scientifically meaningful effect sizes to design experiments with type II error control. Here we present estimates of intra-and inter-subject variances for region of interest (ROI) from resting cerebral blood flow (CBF) maps obtained using whole brain, spin echo echoplanar (SE-EPI) continuous arterial spin labeling (CASL) imaging on 52 elderly subjects (age = 70.5 ± 7.9 years, 29 males). There was substantial intrasubject systematic variability in CBF of gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
(49 reference statements)
4
24
0
Order By: Relevance
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…In order to visualize how much larger or smaller the inter-vendor SDΔCBF was than the intra-vendor SDΔCBF, a voxel-wise variation ratio map was created according to the following equation (Asllani et al, 2008):…”
Section: Data Analysis: Voxel-based Comparisonmentioning
confidence: 99%
“…This step assumes ATT to be homogenously distributed within a slice with an initial value given to the first slice, which is then linearly incremented with superior slices. Here, this step was modeled as: ATT n = ATT 1 + 112 (n-1) ms, where: n = slice number, ATT 1 = ATT of the first slice = 200 ms (Parkes and Tofts, 2002), and 112 ms = the ATT increment per slice computed as the average of findings of Parkes and Tofts (2002) and Asllani et al (2008b).…”
Section: Assessment Of the Effect Of Att On Cbf Quantificationmentioning
confidence: 99%
“…Instead, ATT is modeled based on two main assumptions: (1) within-slice homogeneity, and (2) linear increase with superior slices (Asllani et al, 2008a;Asllani et al, 2008b;Kimura et al, 2004;Parkes et al, 2004). The effects of these assumptions on quantification of CBF are shown in Figure 2A, in which CBFd images obtained based on modeled ATT were compared with those experimentally acquired at each voxel, independently.…”
Section: Quantification Of Cbf and Regional Heterogeneity Of Attmentioning
confidence: 99%